2023
DOI: 10.1111/aos.15678
|View full text |Cite
|
Sign up to set email alerts
|

Bruch's membrane and Brücke's muscle in the pars plana region

Abstract: PurposeTo examine Bruch's membrane (BM) in association with the longitudinal part of the ciliary muscle (LPCM) in the pars plana region.MethodsUsing light microscopy, we histomorphometrically assessed BM and the LPCM in the pars plana region.ResultsThe histomorphometric study included 51 eyes (51 patients; mean age: 60.8 ± 15.0 years; axial length: 26.0 ± 3.3 mm; range: 21.0–36.0 mm). The LPCM (total length: 4.60 ± 1.10 mm) ended 1.15 ± 0.56 mm anterior to the ora serrata. Within the pars plana region, the LPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…As also described in detail previously, we also determined the length of the longitudinal part of the ciliary muscle, the distance between the end of the longitudinal part of the ciliary muscle and the ora serrata, the length of the pars plana region and pars plicata region of the ciliary body, and Bruch’s membrane thickness in the pars plana region. We noted the presence of cobble stones in the fundus periphery, macular Bruch’s membrane defects or and of scleral staphyloma 9 .
Figure 1 Histo-photograph showing the ciliary body of an enucleated human eye with open anterior chamber angle.
…”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…As also described in detail previously, we also determined the length of the longitudinal part of the ciliary muscle, the distance between the end of the longitudinal part of the ciliary muscle and the ora serrata, the length of the pars plana region and pars plicata region of the ciliary body, and Bruch’s membrane thickness in the pars plana region. We noted the presence of cobble stones in the fundus periphery, macular Bruch’s membrane defects or and of scleral staphyloma 9 .
Figure 1 Histo-photograph showing the ciliary body of an enucleated human eye with open anterior chamber angle.
…”
Section: Methodsmentioning
confidence: 94%
“…Although numerous studies have examined the light microscopical and ultrastructural anatomy of the ciliary body including the ciliary muscle and the ciliary processes, the size of the CBS in general, and in dependence of the morphology of the anterior chamber angle in particular, has not extensively been explored yet, except for a study conducted by Ueno and Naumann in 1989 1 9 , 11 15 . Examining eyes with secondary glaucoma, mostly with an anterior chamber closure, Ueno and Naumann reported that the mean thickness of the ciliary muscle was smaller (P < 0.001) in the glaucomatous group than in a group of eyes with malignant uveal melanoma 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation